Lines in the water : nature and culture at Lake Titicaca - Orlove, Benjamin S. (University of California Press, 2002)
This beautifully written book weaves reflections on anthropological fieldwork together with evocative meditations on a spectacular landscape as it takes us to the remote indigenous villages on the shore of Lake Titicaca, high in the Peruvian Andes. Ben Orlove brings alive the fishermen, reed cutters, boat builders, and families of this isolated region, and describes the role that Lake Titicaca has played in their culture.